Hemorrhagic Shock in a Patient with a Morel-Lavallée Lesion Combined with Active Arterial Bleeding without Fracture - Eic Ju Lim; Jong-Keon Oh; Jae-Woo Cho; Seungyeob Sakong; Jun-Min Cho (Journal of Trauma and Injury, 2021)
A Morel-Lavallée lesion is a closed degloving injury caused by traumatic separation of the skin and subcutaneous tissue from the underlying fascia. However, since physicians tend to focus on treating the bone fracture, hemodynamic instability accompanying a Morel-Lavallée lesion can sometimes be overlooked. We report the case of a hemodynamically unstable 73-year-old man who had a Morel-Lavallée lesion of the thigh, but no femur fracture. Angiography showed active bleeding from the muscular branch of the right deep femoral artery, which was then successfully embolized.